The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1007/s11064-022-03800-z
|View full text |Cite
|
Sign up to set email alerts
|

Stellate Ganglion Block Improves Postoperative Cognitive Dysfunction in aged rats by SIRT1-mediated White Matter Lesion Repair

Abstract: BackgroundPostoperative cognitive dysfunction is a common complication of the central nervous system after surgery, especially in elderly patients. White matter lesions cause cognitive impairment. Although stellate ganglion block (SGB) is an effective intervention for postoperative cognitive dysfunction, the exact mechanism remains unclear. The SIRT1 signaling pathway is involved in the process that SGB alleviates postoperative cognitive dysfunction. However, the underlying mechanisms that SGB improves postope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 93 publications
0
2
0
Order By: Relevance
“…SIRT1 also participates in memory formation by regulating synaptic plasticity [ 56 , 57 ]. It has been found that anesthesia/surgery can cause a decrease in the expression of SIRT1 [ 25 , 58 ]. However, administration of the SIRT1 agonist SRT1720 in mice can reduce the level of inflammatory cells and, more importantly, was able to alleviate synaptic plasticity impairment and postoperative cognitive dysfunction [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…SIRT1 also participates in memory formation by regulating synaptic plasticity [ 56 , 57 ]. It has been found that anesthesia/surgery can cause a decrease in the expression of SIRT1 [ 25 , 58 ]. However, administration of the SIRT1 agonist SRT1720 in mice can reduce the level of inflammatory cells and, more importantly, was able to alleviate synaptic plasticity impairment and postoperative cognitive dysfunction [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…This might provide a theoretical study for selecting the concentration of IL-6 24 h after the operation as a visual evaluation index of the prognosis after SGB. After all, according to the existing literature on SGB and inflammatory response, SGB can improve postoperative cognitive dysfunction, and its mechanism may be through the regulation of silent information regular 1 (SIRT1) -mediated neuroinflammation after SGB and correcting white matter damage to improve postoperative cognitive dysfunction [ 20 22 ]. SGB can improve postoperative atrial fibrillation.…”
Section: Discussionmentioning
confidence: 99%
“…Research indicates that SGB can block the conduction of sympathetic ganglionic fibers, preventing intracranial artery spasms, and leading to the dilation of ipsilateral head and neck blood vessels. Furthermore, by inhibiting sympathetic nerve excitation, SGB can lower blood catecholamine levels and reduce neuropeptide Y release, thereby diminishing the stress response, maintaining hemodynamic stability, regulating cytokine release, and modulating immune cell activity to preserve homeostasis in the body environment [14][15][16][17]. With the straightforward procedure and low incidence of related complications, ultrasound-guided SGB has been extensively utilized in the realms of pain management and anesthesia.…”
Section: Discussionmentioning
confidence: 99%